(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Zhuravska N. S. Problematic a way to intensify the education of students in special disciplines. The considered problem study as a way of activization of activity of students. The certain and generalized features of a technique of study of special disciplines: methodical features of lectures, practical occupations, a seminar, independent work by the example of special discipline.